2014
DOI: 10.1002/jmv.24014
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis E genotype 4 virus from feces of monkeys infected experimentally can be cultured in PLC/PRF/5 cells and upregulate host interferon-inducible genes

Abstract: The understanding of the interaction between hepatitis E virus (HEV) and its host cells has been impeded greatly by the absence of a cell culture system. In this study, an efficient cultivation method was developed in PLC/PRF/5 cells for HEV genotype 4 from the feces of monkeys infected experimentally. Compared to minimal essential medium (MEM), mixed Dulbecco's Modified Eagle's Medium (DMEM)/M199 improved the infection efficiency of HEV in PLC/PRF/5 cells. The incubation time and temperature were set at 6 hr … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 40 publications
1
25
0
Order By: Relevance
“…In addition to HCV or NDV infection, several infections by WNV, hepatitis E virus, influenza A virus, Japanese encephalitis virus, and Sindbis virus are capable of upregulation of human ISG12a or murine Ifi27 (17,27,(39)(40)(41), which suggests that ISG12a/Ifi27 may play a vital role in antiviral innate immunity. Actually, we and other groups have determined the antiviral effects of ISG12a/IFI27 on HCV, NDV, WNV, and mouse hepatitis virus (MHV) infection in vitro or in vivo, though the underlying mechanisms remain unknown (22,24,26,27).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to HCV or NDV infection, several infections by WNV, hepatitis E virus, influenza A virus, Japanese encephalitis virus, and Sindbis virus are capable of upregulation of human ISG12a or murine Ifi27 (17,27,(39)(40)(41), which suggests that ISG12a/Ifi27 may play a vital role in antiviral innate immunity. Actually, we and other groups have determined the antiviral effects of ISG12a/IFI27 on HCV, NDV, WNV, and mouse hepatitis virus (MHV) infection in vitro or in vivo, though the underlying mechanisms remain unknown (22,24,26,27).…”
Section: Discussionmentioning
confidence: 99%
“…The HEV ORF3 protein, on the other hand, has been reported to enhance IFN production [20]. HEV also induced ISG expression in PLC/PRF/5 human hepatoma cells [21] and in A549 human lung epithelial cells [22]. Relevance of these observations to natural infection is uncertain, however, as most of studies were not conducted in hepatocyte cell lines and/or relied on overexpression of viral proteins.…”
Section: Introductionmentioning
confidence: 99%
“…In cell culture, the response of HEV infection to IFN treatment is moderate . Only IFNα exerts a considerable anti‐HEV effect; whereas other types, including IFNβ, IFNγ, IFNλ1, IFNλ2, and IFNλ3, do not show clear antiviral activity against HEV .…”
Section: Immune‐based Therapies For Hevmentioning
confidence: 99%
“…The novel ORF4 protein (nt 2835-3308), which is overlapped with ORF1, is only identified in genotype 1 IFN production may subsequently block the induction of ISG expression. However, in vitro cell culture studies 14,19 as well as studies in mice with humanized liver 20 demonstrated ISG induction upon HEV infections. These results indicate that HEV has developed strategies to dampen IFN induction, but not a complete inhibition.…”
Section: Induction and Antagonism Of Ifns By Hevmentioning
confidence: 99%
See 1 more Smart Citation